Earnings, health and gender empowerment: A study of ready-made garment workers in Bangladesh / Shamima Nasrin - Shamima, Nasrin (2018)
Well-being is an integral part of human life. Focusing on the Ready Made Garments (RMG) workers in Bangladesh, this thesis presents a profound assessment that aims to unravel the determinants of three aspects of the workers’ well-being: earnings, health conditions, and women empowerment. These three aspects are of great importance to the well-being of the workers. Earnings can play an important role in alleviating poverty and enhancing the productivity of the workers by motivating them to work more. Considering the poor health status of low wage workers, it is necessary to find out the determinants of health conditions of the RMG workers. Since 80% of the labour force in the RMG industry constitutes women workers, it is imperative to examine whether employment of the women in this sector has contributed to an increase of empowerment for the women workers. This study employed a structured questionnaire as a primary instrument for data collection. Using face-to-face interviews, 775 interviews were conducted where 560 were females and 215 were males. In the first analytical chapter, the human capital theory and the Mincerian wage function was applied and the results revealed that education and formal on-the-job training were positive and highly significant in all estimations. The results also showed the concavity of labour market experience and earnings. Furthermore, there was a gender earnings gap in the RMG sector. The outcome showed that there was a 64% gap due to the differences in endowments and 36% gap is unexplained. In the second analytical chapter, it was found that the following conversion factors constrained the capability and choice of achieving good health for the RMG workers: high job-related demands, high noise levels, high crowding in the workplace, increased workload, and low level educational attainment. In addition, high job-related rewards and being married had expanded their capability to achieve good health. The outcome also revealed that there were gender differences in terms of their health conditions. In the third analytical chapter, it was noted that the working experience of women workers in the RMG industry positively contributed to the enhancement of all kinds of empowerment. Watching TV, using mobile phones, and a higher level of educational attainment showed positive and significant associations with all the four kinds of empowerment. Finally, the outcome of this study contributes to the existing literature in several ways. This study, has examined three important components of the RMG workers’ well-being, all contained within a single study. As a result of this study, a new understanding of the human capital theory, mainly for low-wage workers, was derived. It appears that using actual experiences instead of potential experiences or age as a proxy, helps to use a better measure than using proxy and supplement the human capital theory. While in general the outcome supports the human capital theory, the evidence of this study showed a lower return to education on the whole, for women more than for men, comparatively. This study was also able to develop a comprehensive framework based on the capability approach and the effort-reward model. This study is the first attempt to consider different dimensions of power and empowerment in a single frame.